Pasteurization of Beer by Non-Thermal Technologies - Milani, Elham A.; Silva, Filipa V.M. (Frontiers in Food Science and Technology, 2022)
The pasteurization of beer occurs at the end of the industrial production, after fermentation. Generally, a mild thermal process (60°C) is employed aiming to inactivate the fermenting yeast and potential spoilage microorganisms, thus extending the beer shelf-life at room temperature. The heat treatment negatively affects the original beer freshness and flavor. In this study, beer pasteurization using emerging non-thermal technologies, namely, high-pressure processing (HPP), pulsed electric fields (PEF), and ultrasound (US), was reviewed, including the effect on microbial inactivation and beer quality. The combination of non-thermal methods with mild heat for more efficient pasteurization of beer was also reviewed. All technologies caused microbial inactivation in beer. However, room temperature HPP treatment was the most efficient method, delivering the minimum 15 PU (pasteurization units) to beer after seconds (e.g., 300 MPa for 27 s), as opposed to thermal and TS treatments which required several minutes, while causing a negative impact on beer sensory. As expected, PEF + heat caused a higher microbial inactivation than PEF alone, and yeast ascospores were more resistant than vegetative yeast cells. Non-thermal PEF (35–45 kV/cm) caused 3–5.8 log reductions in vegetative bacteria. Studies on thermal assisted PEF and ultrasound combined with low heat (50–55°C) showed processing times in the magnitude of microseconds for PEF pasteurization and 0.5–2 min (depending on the temperature) for TS pasteurization. With respect to impact of these technologies on beer quality, HPP, thermosonication (TS), high pressure homogenization (HPH), and dense phase CO2 (DPCD) treatments revealed less effect on beer sensory properties, better retaining the freshness of original beer, compared to thermally processed beers.